2021
DOI: 10.1111/spol.12759
|View full text |Cite
|
Sign up to set email alerts
|

Care earnings in the United States and 24 European countries: The role of social policy and labour market institutions

Abstract: Care occupations are gendered and remain relatively poorly paid, particularly in the United States. Prior research on the 'care penalty' primarily points to individual, relational, and market-valuation factors in explaining the relative earnings of care workers. This study integrates these explanations with a comparative institutional perspective. Using higherquality data and methods than previous comparative research in the field-that is, harmonized micro-data from the Current Population Survey and EU-SILC fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…A vast literature has emphasised that domestic workwhich in its broad definition includes both housework and (non-medical non-qualified) care work (ILO, 2013)enjoys a bad reputation and is traditionally attributed low value (Anderson, 2000;Cox, 2006;Ehrenreich & Hochschild, 2002;Hochschild, 2012;Hondagneu-Sotelo, 2001;Lutz, 2008Lutz, , 2011Parreñas, 2001;Rollins, 1985). Care and domestic workers are typically suffering from the 'care wage penalty' and from an overall devaluation of their work, which goes far beyond the economic argument (Ferragina & Parolin, 2022;Lightman, 2021).…”
Section: The Theoretical Framework Nse In the Domestic Sectormentioning
confidence: 99%
“…A vast literature has emphasised that domestic workwhich in its broad definition includes both housework and (non-medical non-qualified) care work (ILO, 2013)enjoys a bad reputation and is traditionally attributed low value (Anderson, 2000;Cox, 2006;Ehrenreich & Hochschild, 2002;Hochschild, 2012;Hondagneu-Sotelo, 2001;Lutz, 2008Lutz, , 2011Parreñas, 2001;Rollins, 1985). Care and domestic workers are typically suffering from the 'care wage penalty' and from an overall devaluation of their work, which goes far beyond the economic argument (Ferragina & Parolin, 2022;Lightman, 2021).…”
Section: The Theoretical Framework Nse In the Domestic Sectormentioning
confidence: 99%
“…Esping-Andersen suggested that 'the move of women into paid employment implies a double job multiplier, visible on both the consumption and production side of the national accounts ledger' (Esping-Andersen et al, 2002, p. 68). However, a growth of services, especially in the domain of care, goes hand in hand with inequalities (as Esping-Andersen highlights himself; see Ferragina & Parolin, 2022); more consumption of these services means an increase of low-paid jobs. This is particularly true in countries with lower levels of social protection and decommodification.…”
Section: The 'Impossible Marriage' Between Full Employment and Equalitymentioning
confidence: 99%